SURVEY EPIDEMIOLOGI: HUBUNGAN ANTARA PERILAKU KESEHATAN GIGI MULUT DENGAN INDEKS DMF-T LANSIA USIA 45-65 TAHUN DI KECAMATAN KRONJO, KABUPATEN TANGGERANG - Lisa Prihastari; Puteri Mentari Siregar; Rizka Indirasari Nur; Sherly Mentari; Zullia Taftyanti (Odonto : Dental Journal, 2017)
Background: The number of elderly population growing fastly in Indonesia along with the increase of life expectancy. Oral health of elderly people greatly affect the quality of life. Oral health in the elderly is reflected in the number of missing teeth (tooth loss), dental caries and periodontal disease. Objective: To know the relationship of Elderly oral health behavior with DMFT indexMethods: Cross-sectional survey with WHO’s method was done by multistage random sampling at 124 age 45-64 years old in Kronjo sub-district, Tangerang.The data was collected by DMFT examination and the standard questionnaire of WHO survey. Calibration test for four examiners with Kappa value was 0.75Results: The mean score of DMFT was 15.5 is included in the very high category. There was statistically significant association between elderly selfassessmentand toothpaste use with DMFT index (p=0,016; p= 0,009). There was no significant association between sweet consuming and dental pain with mean DMFT index (p = 0.216; p = 0.324)Conclusion: Oral Health Behavior of the Elderly in Kronjo sub-district is stillpoor with a very high score of DMFT that will require immediate attention fromthe government.